Role of stretch-activated channels in light-generated action potentials mediated by an intramembrane molecular photoswitch - Chiara Florindi; Vito Vurro; Paola Moretti; Chiara Bertarelli; Antonio Zaza; Guglielmo Lanzani; Francesco Lodola (Journal of Translational Medicine)
Abstract Background The use of light to control the activity of living cells is a promising approach in cardiac research due to its unparalleled spatio-temporal selectivity and minimal invasiveness. Ziapin2, a newly synthesized azobenzene compound, has recently been reported as an efficient tool for light-driven modulation of excitation-contraction coupling (ECC) in human-induced pluripotent stem cells–derived cardiomyocytes. However, the exact biophysical mechanism of this process remains incompletely understood. Methods To address this, we performed a detailed electrophysiological characterization in a more mature cardiac model, specifically adult mouse ventricular myocytes (AMVMs). Results Our in vitro results demonstrate that Ziapin2 can photomodulate cardiac ECC in mature AMVMs without affecting the main transporters and receptors located within the sarcolemma. We established a connection between Ziapin2-induced membrane thickness modulation and light-generated action potentials by showcasing the pivotal role of stretch-activated channels (SACs). Notably, our experimental findings, through pharmacological blockade, suggest that non-selective SACs might serve as the biological culprit responsible for the effect. Conclusions Taken together, these findings elucidate the intricacies of Ziapin2-mediated photostimulation mechanism and open new perspectives for its application in cardiac research.